Prophetic Strategic Leadership: An Epistemological Analysis of Islamic Principles in Contemporary Educational Management - Rita Prima Bendriyanti; Iwan Aprianto; Saihan Saihan; Asnawan Asnawan (FALASIFA : Jurnal Studi Keislaman, 2026)
The leadership crisis in Islamic educational institutions reflects the structural inadequacy of secular–materialistic paradigms in addressing the transcendental and ethical dimensions essential for sustainable institutional excellence. This study aims to: (1) derive strategic leadership principles from the Qur'an and Prophetic traditions (Sunnah) using classical istinbāṭ methodology; (2) critically evaluate Western leadership theories through an Islamic epistemological lens; and (3) construct an integrative model of Islamic strategic–transformational leadership grounded in tawhidic ontology. Employing a philosophical–conceptual approach integrated with systematic literature review, Qur'anic verses were identified through thematic exegesis (tafsir mawdu'i), hadith were authenticated via isnad analysis cross-referenced with the Sahihayn, and normative principles were extracted through three sequential istinbāṭ steps: textual identification, linguistic-contextual analysis, and comparative epistemological evaluation against Western theories. Findings reveal three core dimensions: Qur'anic leadership is ontologically anchored in khalifah fil ardh, syura, and amanah; Western leadership theories are epistemologically constrained by secular–anthropocentric assumptions that marginalize spiritual accountability (hisab ukhrawi); and the Prophetic model integrates long-term strategic vision (ru'yah ba'idah) with transformational moral agency (akhlaq tahwiliyyah). The proposed integrative model constitutes a coherent civilizational alternative offering actionable frameworks for Islamic educational institutions navigating contemporary organizational demands while maintaining epistemological fidelity to revealed sources.